1998
DOI: 10.1523/jneurosci.18-24-10525.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Connection from Cortical Area V1 to V5: A Light and Electron Microscopic Study

Abstract: Area V5 (middle temporal) in the superior temporal sulcus of macaque receives a direct projection from the primary visual cortex (V1). By injecting anterograde tracers (biotinylated dextran and Phaseolus vulgaris lectin) into V1, we have examined the synaptic boutons that they form in V5 in the electron microscope. Nearly 80% of the target cells in V5 were spiny (excitatory). The boutons formed asymmetric (Gray's type 1) synapses with spines (54%), dendrites (33%), and somata (13%). All somatic targets and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
73
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 62 publications
(83 reference statements)
14
73
0
Order By: Relevance
“…Boutons are usually recognized as beads along an axon (bouton en passant) or swellings on short processes extending from the axon (bouton terminaux). Using correlated LM and EM we have repeatedly verified here, and in previous studies (Anderson et al, 1998;Anderson and Martin, 2002, 2005, 2006 that boutons identified at light microscope level form synaptic specializations and that synapses in the interbouton segments are rare.…”
Section: V2 To V1supporting
confidence: 84%
See 1 more Smart Citation
“…Boutons are usually recognized as beads along an axon (bouton en passant) or swellings on short processes extending from the axon (bouton terminaux). Using correlated LM and EM we have repeatedly verified here, and in previous studies (Anderson et al, 1998;Anderson and Martin, 2002, 2005, 2006 that boutons identified at light microscope level form synaptic specializations and that synapses in the interbouton segments are rare.…”
Section: V2 To V1supporting
confidence: 84%
“…Collections of serial sections were digitized and reconstructed using Trakem, an in-house EM-digitization package. To measure and display the postsynaptic densities of labeled boutons we used software developed by ourselves, which has been described in outline previously [see Anderson et al (1998), their Materials and Methods]. We used a Philips CM100 electron microscope fitted with a Morada camera and ITM software.…”
Section: Methodsmentioning
confidence: 99%
“…As shown here, these long-distance connections are important in characterizing the connectivity of regions and the individuality of the connectivity profiles of areas. It remains to be seen whether long-distance connections exhibit unique properties, such as synaptic morphologies (40) or molecular identities of the parent neurons (27,41,42). Overall, the present results point to the need to fully embrace the large-scale connectivity of the cortex if we are to resolve how its overall structural complexity relates to its function.…”
Section: Discussionmentioning
confidence: 78%
“…Based on NNF labeling in the newborn marmoset, which is an indicator of pyramidal cell maturation, existing projections from V1 to area MT at birth are immature (Bourne et al, 2005). In addition, PV labeling, a marker for onset of neuronal activity (Hendrickson et al, 1991), is not present until between P7-P14 in layer 3C of V1 and layer 4 of MT (the V1 recipient layer) (Rockland 1989(Rockland , 1995Anderson et al, 1998). It is not until P90, the start of the "critical period" in the marmoset (Missler .…”
Section: Discussionmentioning
confidence: 99%
“…We specifically examined layer 3C of V1 as well as the input layers 3 and 4 of area MT with which both PIm and V1 terminate. The pulvinorecipient layer in area MT is primarily in deep layer 3 (Spatz, 1975;Trojanowski and Jacobson, 1976;Rockland 1989Rockland , 1995Anderson et al, 1998;Rockland et al, 1999).…”
Section: Cellular/laminar Maturation Of V1 and Area Mtmentioning
confidence: 99%